Multi-dimensional spatial sound design for 'On the String' - Lindborg, PerMagnus (2011)
“On the String” is an installation-performance scored for sound sculptures, real-time synthesis, musicians, light display and an immersive sound diffusion system. The composition, inspired by String Theory, called for the design of an immersive sound design that could be flexibly adapted to different diffusion situations. The software design aimed to realise a concept of sonic objects moving in four-dimensional space. The paper describes loudspeaker setup and software implementation of the work.